Perbedaan Gender dalam Persepsi Karier Remaja Kendari: Pendekatan Analisis Rasch - Wa Ode Lili Andriani Nasri; Sri Kusniawati; Sarniatin Sarniatin; Nurul Meirida; Rahmawati Nur; Nur Zahrah Doane; Sitti Mutaminah; Salwa Amelia (Journal of Multidisciplinary Learning, 2026)
This study aims to eximine the perceptions of male and female students regarding career planning, eith the goal of contributing to the development of career guidance strategies that are responsive to gender-spesific needs. A descriptive qualitive approach was employed, and data were collected an online questionnaire distributed via Google Forms. The participants consisted of 208 senior high school and vocational high school student in Kendari, Indonesia. Data anlaysis was conducted using Rasch modelling to identify perceptual differences between male and female students. The result reveal that male students tend to more frequently envision future success and demonstrate greater reliance on parental involvement in their career planning. In contrast, female student appear to be more proactive in pursuing extracurricular cources outside of school to support their carrer aspirations. The findings also underscore the significant influence of peers and family in shaping student’ career decision-making processes, as well as prevalling tendency among students to depend on luck rafther the enganging in well-strucured planning. Despite these challenges, the study also indentifies encouranging developments, sch as student intiative to enhance additional skills, consideration of multiple factors on career selection, and the presence of crearly defined goals regarding higher education pathways.